Looking for Mr GoodWill in “Rancho Grande” and Beyond: The ‘Ghostly’ Presence of Shakespeare in Mexican Cinema - Michel Modenessi, Alfredo (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2012)
The Perhaps as an outcome of the “globalization” of Shakespeare studies, the film Huapango (dir. Iván Lipkies, 2003), avowedly based on Othello, seems to be drawing attention from scholars world-wide far more quickly and productively than the only other movie unabashedly adapted from a Shakespeare play in Mexican cinema: Cantinflas’s Romeo y Julieta (dir. Miguel M. Delgado, 1943). Although in Mexico these two pictures still stand alone in deriving integrally from a Shakespeare play, they are not, of course, the sole cases in Spanish-speaking cinema, where over the years a handful of films have been made with similar premises. All of them share a simple but potentially revealing feature, however: so far, no Spanish-speaking film made from Shakespeare can be deemed a “straightforward” performance/translation of its source. Nonetheless, films that ‘reset’, ‘cite’, or somehow ‘ex/ap-propriate’ Shakespeare are not wanting in Mexico. After briefly revisiting points I have made elsewhere on the two aforementioned pictures, this mostly descriptive paper* will aim to identify the “actual” or “ghostly” “presence” of Shakespeare in three films made at diverse stages in the history of Mexican cinema: Enamorada (dir. Emilio Fernández, 1946), El charro y la dama (dir. Fernando Cortés, 1949), and Amar te duele (dir. Fernando Sariñana, 2002).